Ecology Control and Economic Development in East African History the case of Tanganyika, 1850-1950 - Kjekshus, Helge (Dar es Salaam Mkuki na Nyota, 1996)
This pioneering book was one of the first to place the history of east Africa within the context of the environment. It has been used continously for student teaching. It is now reissued with an introduction placing it within the debate which had developed on the subject;there is also an updated bibliography.
Includes index.
Keywords: Ecology-Tanzania